Prediction of air pollutant effects from external sources using Gaussian dispersion model - Mehrabi, H.; Ramli, N.A.; Zinatizadeh, A.A.; Isa, M.H. (2005)
Industrial, urban and traffic pollution have been growing from a few years in most Iranian areas. Kermanshah is located in the west of Iran where has been recently industrialized by polluted industries such as cement factory, thermal power plant and many asphalt factories outside the city. This city and its surrounding are inhabited by more than one million people. Emission characteristics of two polluted industries were seasonal characterized in order to determine air pollution loading caused by industrial activities around of the city, then Gaussian model was employed for predicting the ground level concentration of Dust at various distances downwind of emission sources and the impact of main existing sources on urban area and plume rise was computed by two methods, Holland and Briggs, in two stability A and D at two seasons, summer and winter. Based on pollutant dispersion model, cement factory has been considered as a pollutant source in terms of Dust. According to the results obtained from calculation of Dust ground level concentrations by Gaussian dispersion model, asphalt factory had no significant effect on air quality of the city.